Biological properties and vector competence of Diaphorina citri for Candidatus Liberibacter asiaticus modulated by an insect-specific virus - Diogo M. Galdeano; Tanvi Rawat; William Ingram; Curtis R. Carlson; Gustavo Rodrigues Alves; Yen-Wen Kuo (iScience, 2025)
Summary: Insect-specific viruses (ISVs) infect only insects and have been studied primarily in mosquitoes. Here, we extend the concept of ISVs to include those found in plant-feeding insect vectors, such as Diaphorina citri, the vector of Candidatus Liberibacter asiaticus (CLas), the causal agent of citrus Huanglongbing. Using Diaphorina citri flavi-like virus (DcFLV) as a model, we examined its effects on host biology and CLas transmission. DcFLV infection delayed development and preoviposition and reduced feeding activity, whereas overall survival, oviposition, and sex ratio were unaffected. DcFLV-infected D. citri transmitted CLas with ∼20% greater efficiency than uninfected controls, despite no significant difference in CLas titers. These findings suggest that ISVs can modulate the transmission dynamics of plant pathogens by insect vectors, adding complexity to vector-pathogen interactions.